2022
DOI: 10.3390/antiox11091842
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Knowledge in Biological Properties of Cirsimaritin

Abstract: The search for natural plant-based products as new pharmacological alternatives to treat various human pathologies has taken on great importance for researchers and research laboratories. In this context, research has intensified to extract and identify natural molecules endowed with biological effects. The objective of this study is to review the source and pharmacological properties of cirsimaritin. The identification and isolation of this flavonoid from various natural sources, including medicinal plants su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Tannins, triterpenes, triterpenoids, and flavonoids from many plants can cause irreversible inhibition of several resistant bacterial strains, including Staphylococcus species, by altering the bacterial cell membrane permeability and fluidity, leading to a final damaging effect on the bacterial cell membranes [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The chemical analysis of the Cynoglossum tubiflorus leaf methanolic extract showed high contents of phenolic compounds, flavonoids, and lignans, such as chlorogenic acid, rosmarinic acid, cirsimaritin, kaempferol, and cinchonain Ib, described for their antibacterial activities [ 46 , 59 , 60 , 61 , 62 , 63 ]. For instance, kaempferol [ 64 ] has already been described as a compound that can destroy the bacterial membranes of S. aureus in a murine corneal infection model.…”
Section: Resultsmentioning
confidence: 99%
“…Tannins, triterpenes, triterpenoids, and flavonoids from many plants can cause irreversible inhibition of several resistant bacterial strains, including Staphylococcus species, by altering the bacterial cell membrane permeability and fluidity, leading to a final damaging effect on the bacterial cell membranes [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The chemical analysis of the Cynoglossum tubiflorus leaf methanolic extract showed high contents of phenolic compounds, flavonoids, and lignans, such as chlorogenic acid, rosmarinic acid, cirsimaritin, kaempferol, and cinchonain Ib, described for their antibacterial activities [ 46 , 59 , 60 , 61 , 62 , 63 ]. For instance, kaempferol [ 64 ] has already been described as a compound that can destroy the bacterial membranes of S. aureus in a murine corneal infection model.…”
Section: Resultsmentioning
confidence: 99%
“…Cirsimaritin has been reported to possess multiple biological effects, including antimicrobial, anti-inflammatory, and antiproliferative properties. It can also be used as an antidiabetic [ 47 ]. Isorhamnetin has an extensive pharmacological effects such as cardiovascular protection, anti-inflammation, anti-tumor, anti-oxidation, anti-bacterial, and anti-virus.…”
Section: Resultsmentioning
confidence: 99%
“…This inhibition, in turn, led to reduced levels of proinflammatory cytokines and decreased expression of iNOS and COX-2, effectively preventing inflammation induced by DSS in the colon. Furthermore, a recent study revealed that cirsimaritin exerts anti-inflammatory activity by inhibiting nitric oxide production, inducing the expression of nitric oxide synthase, and blocking various cytokines, including IL-6 and TNF-α ( Benali et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%